Perseverance, hard work pay off for ex-teacher - Sunday Star (2004)
BANGI : Determined to improve the field of special education in the country, Dr Gunasegaran Karuppannan set out to conduct a four-year research on hearing-impaired pupils, which earned him a PhD.